GTOP-PELLET: Green torrefied oil palm pellet - Sambeth, Sharwin Kumar; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (2021)
Malaysia as world second largest producer of palm oil. An oil palm tree consist 79% of biomass such as oil palm frond (OPF), empty fruit bunch (EFB), palm kernel shell (PKS), palm mesocarp fiber (PMF) and Oil palm trunk (OPT).